Renewal Of The National Criminal Law With The Soul Of The Nation’s Cultural Values - SAMBAS, N. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT Each country has its legal system, which is not sourced from the cultural values of its people but was abandoned (the inheritance of its colony), especially countries that became independent after World War 3, as experienced by Indonesia. The purpose of this article is that future criminal law is in line with the development of international society, but still upholds the noble values and culture of the nation itself. Therefore, in carrying out reforms, one must pay attention to and fulfill the fundamental philosophical, juridical, sociological basis. RESUMEN Cada país tiene su sistema legal, que no proviene de los valores culturales de su gente, sino que fue abandonado (la herencia de su colonia), especialmente los países que se independizaron después de la Tercera Guerra Mundial, como lo experimentó Indonesia. El propósito de este artículo es que el derecho penal futuro esté en línea con el desarrollo de la sociedad internacional, pero aún defiende los nobles valores y la cultura de la nación misma. Por lo tanto, al llevar a cabo reformas, se debe prestar atención y cumplir con las bases filosóficas, jurídicas y sociológicas fundamentales.